A Memória da Guerra civil espanhola no Cinema: o caso de El Labirinto del Fauno, de Guillermo del Toro - Cortada, Isabella Alessandra (CEM – Cultura, Espaço & Memória, 2020)
Being the collective memory a social construct and a factor of identity for any community, how are we supposed to live with oblivion? How are we to live upon the deletion of the past (de‑memorizing)? Amidst the dispute at what to remember, it is possible to think of underground memories that express the spoken word of the excluded and of the neglected from the official memory. Shaping a new perspective on History accounts, innumerous filmakers consecrated their art to the experience of memory and the uses of oblivion. Amongst the many possible, we call upon Guillermo del Toro and his Labirinto del Fauno from 2006.